Evaluation of P53 gene expression by immunohistochemistry to diagnosis oral precancerous lesions - Wang, Ling; Qi, Fengna; Hao, Lele; Sun, Honglei (Cellular and Molecular Biology, 2021)
Oral Precancerous lesions include leukoplakia, erythroplakia, and mucosa palate changes due to reverse smoking. Assessing the prevalence of these lesions in a cross-sectional study can be effective in the timely prevention and treatment of lesions, in any community. Hence, in the present study, evaluation of P53 gene expression was done by immunohistochemistry method to diagnosis oral precancerous lesions. For this purpose, 111 Chinese patients (54 women and 57 men) were selected for examination. The age range of these patients was 22 to 69 years, and their average age was 32.6 years. All patients were examined by one physician. Oral mucosa was used for immunohistochemical evaluations. All samples taken from patients' mucosa were evaluated by one pathologist under a light microscope. 80 cases of the 111 patients were smokers and 27 were non-smokers. Among the 80 smokers, 56.25% had leukoplakia, 3.75% had erythroplakia, and 40% had mucosa palate changes. Regarding non-smokers, 74.07% had leukoplakia and 25.93% had erythroplakia. None of the non-smokers had mucosa palate changes. In terms of the lesion location, in patients with leukoplakia 89.23%, and patients with erythroplakia 90% of the lesion was located in the cheek mucosa and buccal vestibule. Also, in patients with leukoplakia 9.23%, and patients with erythroplakia 10% of the lesion was located in the lips vestibular mucosa. Only 1.54% of leukoplakia had a lesion in the vermilion border, and none of the erythroplakia patients had a lesion on the vermilion border. 76 patients (68.46%) showed positive expression of the P53 gene. The expression level of the P53 gene did not show a significant relationship with age, and the genders did not have a statistically significant difference in terms of gene expression. The expression level of the P53 gene was 59.8% in leukoplakia, 70% in erythroplakia, and 40% in Mucosa palate changes. The present study showed that the evaluation of P53 gene expression was well able to detect oral precancerous lesions and their severity by increasing their expression rate.